PSYCHOLOGICAL AND PEDAGOGICAL FOUNDATIONS OF FORMATION ARTISTIC PERCEPTION AND THE DEVELOPMENT OF THE CREATIVE IMAGINATION OF SCHOOLCHILDREN IN FINE ARTS LESSONS - Razzoqovna, Ostonova Gulshod (The journal of contemporary issues in business and government, 2021)
The article says that the development of human cognitive abilities is a value that is generally recognized in the modern world. At the same time, scientists have recently expressed their serious concern about the formation of a harmonious, creatively active person who is able to solve the problems that constantly arise in the modern world. In addition, in modern art pedagogy, the development of cognitive processes and human abilities for the creative processing of impressions from the world around them is understood as the formation of an integral system of creative qualities of perception, thinking and memory.